Multisectoral economic models for developing countries - David P. Vincent (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1981)
A feature of the economies of many less developed countries (LDC's) is their heavy reliance for foreign exchange earnings on a few export commodities whose markets are characterised by low income elasticities on the demand side and whose supply is continually expanding under the influence of improved production technologies while remaining highly sensitive to year weather conditions. Given these commodity market characteristics, such economies, unless they reduce their high export concentration in these commodities, are faced with both an unstable export earnings pattern and a long run deterioration in their terms of trade. It is not surprising therefore that these countries have in recent years under the guidance of the UNCTAD Secretariat, shown increasing interest in proposals to conclude international commodity agreements or producer cartels in selected commodity markets with the aim of both raising the prices of the commodities concerned and reducing their year to year variability. Implicit in such proposals is an attempt to at least halt if not reverse the flow of resources from the less wealthy producing countries to the more wealthy consuming countries which is taking place through the decline in many low energy content raw materials prices relative to world commodity prices in general. The central task of this paper is to specify a model system capable of addressing the above issues. In outline the entire system consists of a set of individual country models each linked to a single entity (interpreted as the rest of the world) via a set of rest of the world demand and supply equations for the commodities produced by each country. The framework makes no provision however for formal linkages between specific country models. Only one system of country model equations is specified. This system has however sufficient flexibility to accommodate the relevant country specific structural and institutional features. Since the central aim of the project is to quantify and explain the economic implications across countries of a given exogenous shock, the choice of a unique model design ensures that variations in response across /countries can be attributed solely to specific features of each economy and not to differences in model specification. Furthermore, by working with a single framework computing requirements are greatly simplified.
Keywords: 330